Conditioned medium: a new alternative for cryopreservation of equine umbilical cord mesenchymal stem cells - Maia, Leandro [UNESP]; Dias, Marianne Camargos [UNESP]; Moraes, Carolina Nogueira de [UNESP]; Freitas-Dell'Aqua, Camila de Paula [UNESP]; Silveira Da Mota, Ligia S. L. [UNESP]; Santiloni, Valquiria [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Wiley-Blackwell, 2017)
Cryopreservation is a feasible alternative to maintaining several cell lines, particularly for immediate therapeutic use, transportation of samples, and implementation of new in vitro studies. This work parts from the hypothesis that the medium of cryopreservation composed by 90% of conditioned medium (CM) supports cryopreservation of equine umbilical cord intervascular matrix mesenchymal stem cells (UCIM-MSCs), allowing the maintenance of the biological properties for the establishment of cell banks intended for therapeutic use and in vitro studies. Thus, we evaluated the viability, apoptosis/necrosis rates, immunophenotypic profile (IP), chromosomal stability, clonicity, and differentiation potential of UCIM-MSCs cryopreserved with four different mediums (with FBS: M1, M3, M4 and without FBS: M2). After 3 months of cryopreservation, samples were thawed and analyzed. The potential of differentiation in the mesodermal lineages, clonicity, and the chromosomal stability were maintained after cryopreservation of UCIM-MSCs with medium containing FBS. Changes (P < 0.05) at IP for some markers were observed at cells cryopreserved with medium M1-M3. Only the UCIM-MSCs cryopreserved with the CM (M4) had similar viability post-thaw (P = 0.23) when compared with fresh cells. We proved the hypothesis that the medium of cryopreservation containing CM supports the cryopreservation of UCIM-MSCs, at the experimental conditions, being the medium that better maintains the biological characteristics observed at fresh cells. Thus, future studies of UCIM-MSCs secretome should be conducted to better understand the beneficial and protective effects of the CM during the freezing process.
Keywords: cell banks; fetal adnexa; freezing; horse; MSCs; viability